IMPACTS OF COVID-19 ON BANGLADESH ECONOMY: IS THE POST COVID-19 BANGLADESH ECONOMY RISKY? - HOSSAIN, Sharif (Journal of European Economy, 2021)
In this study, the principal purpose has been to investigate the impacts of COVID-19 on GDP, export volumes, remittance and unemployment of Bangladesh and to forecast these variables for a period of time using econometric techniques. The results show that the loss of GDP, export volumes and remittance of Bangladesh in 2020 will be 40984.3387 million, 6540.966 million, 3941.449 million respectively. In terms of percentage, the loss of GDP is 18.08%, export volumes – 18.08%, and remittance – 19.73% of the total values. The predicted values indicate that the Bangladeshi GDP, export volumes and remittance inflows will fall for 3 years, 2 years and 2 years respectively. Due to COVID-19 outbreak, the loss of world GDP will be 14904846.597 million dollars or 17.07% of the total GDP and will experience decrease for 7 years. Thus, Bangladeshi economy will face downturn for a lesser period than the world. The predicted GDP shows that COVID-19 will result in a decline of Bangladeshi GDP and export volumes until 2021, after which they will be have an increase rate of 4.7% and 9.8% respectively. Additionally, prediction of the remittance inflows reveals a decline in 2020, but an increase of 6.692% for 2021. It is also concluded that in 2020 global unemployment rate will be increase by 1.36%, while the unemployment rate in Bangladesh will be increase by 58.23%. This indicator for Bangladesh is very high, but it will fall by 18.72% in 2021 and starting with 2022 it will be increasing by 2.47% for a long period of time. Thus, it can be said that COVID-19 will be a big threat for increasing the unemployment rate for a long period of time. The research testifies that the death rate with respect to confirmed cases is statistically significant at any level. Finally, as no economic indicators other than the unemployment rate will be unreasonably affected, the post COVID-19 economy of Bangladesh will not face undue risk. JEL: C12, C13, C23, C32, C33, C51, C52, C53, C54, C55, O11, O50, O57, Q40.